Computer control of real-time processes - Bennett, S. (Stuart).; Virk, G. S. (Gurvinder S.). (London P. Peregrinus on behalf of the Institution of Electrical Engineers, 1990)
The following topics are dealt with: discrete controller design; multivariable control system design; PID controllers; sequences for control; real-time computer networking; parallel processing; computer control; software design; real-time system; real-time software; software fault tolerance; shop floor control systems; batch process control; and other control applications.
Electronic reproduction.
Keywords: Process control -- Data processing; Automatic control -- Data processing; Real-time control